Recent topics of pharmacology in oriental medicine : detoxification of morphine addiction in the mouse narcotic dependence model using extracts from psidium guajava leaves - Lutterodt, George Daniel (1999)
The effects of a polar fraction of an extract from the leaf of the guava plant, Psidium guajava Linn (Myrtaceae), including the effects of two isolated flavonoid compounds, quercetin and quercetin-3-arabinoside, on withdrawal symptoms in morphine-dependent mouse models were studied. Two types of mouse narcotic-dependence models were employed.Mouse chronic narcotic-dependence model was prepared by thrice daily 1.p injection of morphine sulphate, with an initial dose of 4 mg/kg and increasing each successive dose by 4 mg/kg, up to day-9, when the dose of 108 mg/kg reached was maintained through day-11 and the morning of day-12.Mouse acutely narcotic-dependence model was prepared by a s.c. bolus injection of 50 mg/kg morphine sulphate, followed 4 h later by s.c. injection of 10 mg/kg naloxone. Manifestations of abstinence syndrome, characterised by repetitive vertical jumping,rearing,paw-shaking,head-shaking,teeth chattering,etc.,occurred about 14 h after the last dose in group A,and 45 - 60 min after naloxone injection in group B.A s.c. dose of 0.5 mg/kg of the extract, 10 h after the last dose in group A or 1 h before the naloxone injection in group B, prevented the repeated vertical jumps and greatly reduced the other symptoms of withdrawal.Parallel experiments on satiety to the extract in mice showed no development of dependence on the extract. Quercetin may be the main active compound in the extract.